Algorithm for monitoring patients with axial spondyloarthritis depending on the activity of the disease - A. V. Datsina; Sh. F. Erdes (Современная ревматология, 2025)
Axial spondyloarthritis (axSpA) is actively treated with biologic disease-modifying antirheumatic drugs, but their efficacy decreases over time, leading to the development of exacerbation, the onset of severe and chronic pain, progression of structural changes and deterioration of quality of life, as well as significant economic losses. The international community is increasingly concerned about the problem of identifying difficultto-treat (D2T) patients. In this context, it is necessary to develop strategies and markers for their identification and effective treatment. The authors propose a regimen of follow-up that represents an innovative approach to monitoring patients with D2T axSpA.